Answer:
It is 3y = 4x + 10
Explanation:
Let's first get the slope of the curve.
[ slope is the derivative of the equation ]
![{x}^(2) - xy + {y}^(2) = 7](https://img.qammunity.org/2022/formulas/mathematics/high-school/dxf6vls0huybf2k0u6zue9cxx99z1bbem4.png)
introduce dy/dx :
![(d)/(dx) ( {x}^(2) - xy + {y}^(2) ) = (d)/(dx) (7) \\ \\ 2x - (y + (dy)/(dx) ) + 2y (dy)/(dx) = 0](https://img.qammunity.org/2022/formulas/mathematics/high-school/64mh9aqhkc3jrjon6ya8kajhr40vfkhjnb.png)
make dy/dx the subject:
![2x - y - (dy)/(dx) + 2y (dy)/(dx) = 0 \\ \\ 2y (dy)/(dx) - (dy)/(dx) = y - 2x \\ \\ (dy)/(dx) (2y - 1) = y - 2x \\ \\ (dy)/(dx) = (y - 2x)/(2y - 1)](https://img.qammunity.org/2022/formulas/mathematics/high-school/e2xee80dy51rvw6x42jjhaehy7ftjn4991.png)
At point (-1, 2):
![(dy)/(dx) = (2 - 2( - 1))/(2(2) - 1) \\ \\ slope = (4)/(3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/lytbh24d2txy2f7za6uc6r5zy1rmwacl2z.png)
but a tangent has the same slope as the curve:
![y = mx + c](https://img.qammunity.org/2022/formulas/mathematics/high-school/mpsydhdqmt6eheycm3xmw9eeme8fwkngx1.png)
m is the slope
c is the y-intercept
At (-1, 2):
![2 = ( - 1 * (4)/(3) ) + c \\ \\ c = 2 + (4)/(3) \\ \\ c = (10)/(3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/se9glijwqz4zv15bt67lqn4nbtc8xk28cx.png)
equation:
![y = (4)/(3) x + (10)/(3) \\ \\ { \boxed{3y = 4x + 10}}](https://img.qammunity.org/2022/formulas/mathematics/high-school/6wrbr2ph2hjya9c54el4p5r9xjl41t0tc7.png)